Solo en la encrucijada soy un centro. Experiencias de escritura creativa: atisbo autoetnográfico - Márquez Vargas, Vanessa Alejandra (2024)
The text highlights the versatility and purposes of creative writing as a means to recreate experiences, explore emotions, providing perspective and meaning to the written reality, through a creative writing workshop experience that emerged as a result of the COVID-19 pandemic lockdown in 2020; an experience that served therapeutic purposes for the participants, also glimpsing an autoethnographic experience for their facilitator. The aim is to emphasize the practice of creative writing, using literary, psychological techniques and tools to stimulate the transformation of an idea into a sensation and then into a narrative. The text finally points out that writing is a form of personal and social affirmation. Creative writing is a useful mechanism for recognizing sensitivity, giving rise to a multiplicity of voices and perspectives in creation beyond classifications in genres or discursive typifications.